2020
DOI: 10.1186/s12974-020-02033-7
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage to myofibroblast transition contributes to subretinal fibrosis secondary to neovascular age-related macular degeneration

Abstract: Background Macular fibrosis causes irreparable vision loss in neovascular age-related macular degeneration (nAMD) even with anti-vascular endothelial growth factor (VEGF) therapy. Inflammation is known to play an important role in macular fibrosis although the underlying mechanism remains poorly defined. The aim of this study was to understand how infiltrating macrophages and complement proteins may contribute to macular fibrosis. Methods Subretinal fibrosis was induced in C57BL/6J mice using the two-stage la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 38 publications
2
78
0
Order By: Relevance
“…Luo et al identified choroidal pericytes as a source of myofibroblasts in a model of laser-induced CNV and showed that choroidal pericytes play a role in the formation of subretinal fibrosis by expressing ECM components (Luo et al 2018). Finally, myeloid cells such as macrophages transdifferentiate into myofibroblasts in experimental fibrotic kidney disease (Meng et al 2016) and express α-SMA under TGFβ induction in vitro (Little et al In line with these findings, approximately 20% of infiltrating Iba-1 + myeloid cells in human MNV were reported to be immunoreactive for α-SMA, suggesting that MMT is present in macular fibrosis secondary to nAMD (Little et al 2020b) (Fig. 5).…”
Section: Myofibroblasts and The Potential Source Of Myofibroblast Precursors In Subretinal Fibrosismentioning
confidence: 88%
“…Luo et al identified choroidal pericytes as a source of myofibroblasts in a model of laser-induced CNV and showed that choroidal pericytes play a role in the formation of subretinal fibrosis by expressing ECM components (Luo et al 2018). Finally, myeloid cells such as macrophages transdifferentiate into myofibroblasts in experimental fibrotic kidney disease (Meng et al 2016) and express α-SMA under TGFβ induction in vitro (Little et al In line with these findings, approximately 20% of infiltrating Iba-1 + myeloid cells in human MNV were reported to be immunoreactive for α-SMA, suggesting that MMT is present in macular fibrosis secondary to nAMD (Little et al 2020b) (Fig. 5).…”
Section: Myofibroblasts and The Potential Source Of Myofibroblast Precursors In Subretinal Fibrosismentioning
confidence: 88%
“…The study complies with the Declaration of Helsinki and the protocol was approved by the Ethical Review Board of Queen’s University Belfast. The samples were then wax embedded and processed for immunohistochemistry detailed previously by us [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…In both human and murine fibrotic tissues, this activation state is maintained via direct contact enabled by macrophages' cadherin-11 ( 138 ). In addition to their ability to directly stimulate myofibroblasts, recent work has shown that macrophages are capable of transitioning into smooth muscle cells or myofibroblasts in the context of atherosclerosis, subretinal, or renal fibrosis, respectively ( 139 , 140 , 141 ). In conclusion, macrophages are complex and jack-of-all-trades components of the innate response, but their direct interaction with fibroblasts should serve as motivation to manipulate and further understand their role in scarless wound healing and fibrosis.…”
Section: Inflammation and Innate Immune System Cellsmentioning
confidence: 99%